Manajemen Perencanaan, Pengadaan, dan Pengendalian Obat di Instalasi Farmasi Rumah Sakit - Stacey Polii; Jimmy Posangi; Aaltje Ellen Manampiring (Universitas Sam Ratulangi, 2021)
Background: Several hospitals in Indonesia have shown drug vacancies, drug delays, and minimal budgets in drug procurement. The availability of drugs is also influenced by the value of the hospital BOR which fell during the Covid-19 pandemic. The purpose of this research is to analyze the implementation of Permenkes No. 72 of 2016 on the management of planning, procurement, and control of drugs at the pharmacy installation of the GMIM Pancaran Kasih General Hospital, Manado. Methode: This a qualitative research. The research was carried out on March-July 2020. The research location is at the pharmacy installation of the GMIM Pancaran Kasih General Hospital, Manado. This study took 5 informants. Data analysis used content analysis from in-depth interviews, direct observation of documents and comparing with theories in the literature. This study uses validation with source triangulation techniques and methods. Result: The results showed that the planning, procurement and control of drugs at the General Hospital of GMIM Pancaran Kasih is in accordance with the Regulation of the Minister of Health of the Republic of Indonesia No. 72 of 2016 concerning Pharmaceutical Service Standards in Hospitals. It was also found that the e-purchasing system as a whole did not work well because the facilities and infrastructure were inadequate. Conclusion: That can be concluded that the implementation of Minister of Health Regulation No. 72 of 2016 on the management of planning, procurement, and control of drugs at the pharmacy installation of the General Hospital GMIM Pancaran Kasih Manado has been going well. However, it is necessary to add human resources in the pharmaceutical field.